EVALUASI POTENSI GEOWISATA AREA DIENG SEBAGAI KAWASAN GEOPARK NASIONAL - Wicaksono, Muhammad Haston Samudra (Jurnal Media Akademik (JMA), 2024)
Indonesia is the largest archipelagic country in the world which has a great diversity of flora and fauna, arts and culture, geological heritage, historical traces, and other potential that can be developed. One type of tourism that has not been widely utilized in Indonesia is geological tourism, namely geotourism. The Dieng area, Central Java is one of the areas that has the potential to become a national geopark. This research was conducted to evaluate the potential of the Dieng Plateau before it was proposed as a national geopark. The method used in this research is a literature study method with an evaluation carried out in accordance with the requirements for assessing an area that can be proposed as a geopark which includes the presence of geoheritage, geo biodiversity and geo culture. The results of the evaluation carried out stated that the Dieng area has a lot of geoheritage potentials such as Sikidang Crater, Candradimuka Crater, Sileri Crater, Color Lake, Pengilon Lake, Cebong Lake, Bukit Pandang, Mount Sikunir, Jalatunda Well and Batu Ratapan Angin, geo biodiversity in the form of fauna and endemic flora, and geo culture in the form of the Arjuna Temple Area and culture in the form of ruwat rambut gimbal.